Experimental study on the effect of surface evaporation on the thermocapillary-buoyancy convection in a shallow annular pool. (September 2019) - Li, Jin-Jing; Zhang, Lu; Zhang, Li; Li, You-Rong; Quan, Xiao-Jun
Highlights: Effect of surface evaporation on thermal convection was experimentally studied. Critical Marangoni number increases with evaporation rate and liquid pool depth. Surface evaporation and buoyancy effects can suppress the flow destabilization. At a weak evaporation, hydrothermal waves and physical waves are regular. At rapid evaporation, the vapor recoil can directly trigger the flow instability. Abstract: In order to understand effect of surface evaporation on thermocapillary-buoyancy convection, a series of experiments on thermocapillary-buoyancy convection in a shallow annular pool with different surface evaporation rates have been conducted. The annular pool is subjected to a radial temperature gradient, and the inner and outer radii are respectively 20 mm and 40 mm. The 0.65 cSt silicone oil has been selected as the working fluid for its relatively strong volatility. Results show that the surface evaporation rate depends mainly on Marangoni number and the average temperature of the working fluid. At a weak evaporation, the critical Marangoni number increases with the increase of the surface evaporation rate and the liquid pool depth, i.e. the surface evaporation and buoyancy effects can suppress the flow destabilization. When the three-dimensional flow appears, the temperature fluctuation from the hydrothermal waves and the free surface fluctuation of the liquid layer are regular and coincident. However, in the case of the rapid evaporation, the vapor recoil can directly trigger the flow instability. Furthermore, the temperature fluctuation is weakened significantly, and the surface fluctuation of the liquid layer become irregular due to the vapor recoil effect.